(untitled) - Erickson, John R.; 1943-; Holmes, Gerald L. (New York, 2006)
Hank learns about a tool thief on the loose who uses a monkey to help him do his dirty work.
008-up.
Keywords: Fiction; Monkeys; Fiction; Dogs; Fiction; Humorous Stories; Fiction; West (U.S.); Mystery and detective stories; Ranch life; Hank the Cowdog (Fictitious character); Burglars; Fiction; Ranch life; Fiction; Dogs; Fiction; Fiction; Monkeys; Fiction; Hank the Cowdog (Fictitious character); West (U.S.); Fiction; West (U.S.); West (U.S.); Juvenile literature; Western stories; Fiction; Fiction